Against interoperability? Terrains of technopolitical contestation and the remaking of EU border infrastructure - Paul Trauttmansdorff (Big Data & Society)
Digital technologies and databases have repeatedly been associated with grand infrastructural promises in the European Union (EU)'s so-called management of borders and migration. Interoperability, i.e., the capacity to process traveler data across multiple databases, has been widely promoted as the latest and most transformative infrastructural innovation in this context. Yet, the contentious claims, voices of dissent, and opposing views regarding the remaking of this border infrastructure have often been neglected by scholarship on digital borders and interoperability. This article explores how the interoperable data infrastructure of borders has emerged as a point of contestation. It introduces the concept of terrains of technopolitical contestation to examine how multiple claims about interoperability have been articulated and contained. Drawing on interviews and the analysis of online and offline documents, the article identifies three key terrains that have shaped the nature and scope of contentious claims: the parliamentary, consultative, and civil society terrains. The article argues that each of these terrains characterizes the boundaries between the political and technological dimensions of interoperability, producing distinct forms of contestation. This boundary-making process is crucial not only for shaping how claims and issues can be framed but also for limiting the space of critique and critical interventions in the current technopolitics of the EU border regime.